Unusual Course of the Reaction of Lawesson’s Reagent with β-Phosphoryl- β’-carbethoxyhydrazones: First Synthesis of 5-Mercapto-3-(methylthiophosphoryl) pyrazoles - Chebil, Emna; Touil, Soufiane (Letters in Organic Chemistry, 2012)
It is well known that Lawesson’s reagent (LR) reacts with hydrazone derivatives at 80 °C to yield 3-thioxo- 1,2,3-diazaphospholine derivatives. We show, in the present investigation, that the reaction of LR with β- phosphoryl-β’-carbethoxyhydrazones under the same conditions, took an entirely different course and gave a new type of pyrazole derivatives, the 5-mercapto-3-(methylthiophosphoryl)pyrazoles.
Keywords: Lawesson’s reagent